Incorporating Employer’s Requirement in Curriculum Design to Improve the Graduate’s Technical Competence using Quality Function Deployment - Karnain, Dikxy Zul; Widiastuti, Indah; Suharno, Suharno (International journal of pedagogy and teacher education, 2018)
The graduates of vocational pre-service teacher education are expected to possess appropriate pedagogical, theoretical and practical skills. As part of the academic curriculum, all students should do two kind of apprenticeship programs: an industrial training and a teaching practicum at school. These programs providing students with the exposure to a real working environment in the industry and vocational schools. Thorough this program, the industry and the school could assess the student teachers’ competences in their subject-related skills. Therefore, this study aims to identify feedback from the employers during the apprenticeship in order to determine their expectations toward the practical skills of vocational student teachers using Quality Function Deployment (QFD) approach. The employer’ feedbacks are then translated into technical requirements which specifying the actions required in teaching and learning process. The QFD help the education institution to identify the gaps in the curriculum based on the requirements from the school and industry.